Superparamagnetic iron oxide nanoparticles as the sole method for sentinel node biopsy detection in patients with breast cancer. Issue 12 (6th September 2017) - Karakatsanis, A.; Daskalakis, K.; Stålberg, P.; Olofsson, H.; Andersson, Y.; Eriksson, S.; Bergkvist, L.; Wärnberg, F.
Abstract : Background: Sentinel node biopsy (SNB) using superparamagnetic iron oxide (SPIO) nanoparticles is a novel method in breast cancer. Several studies have verified the non‐inferiority of SPIO compared with the standard use of radioisotope 99m Tc with or without blue dye. The aim of the MONOS study presented here was to evaluate the use of SPIO as a sole tracer and the efficacy of tracer injection in the preoperative setting. Methods: This prospective cohort study was carried out in two hospitals, one using 99m Tc and the other SPIO. 99m Tc was injected in the morning of the day of surgery or the day before. SPIO was either injected before surgery in the outpatient clinic or 1 h before the operation. Results: A total of 338 consecutive patients with breast cancer underwent 343 procedures; SPIO nanoparticles were used in 184 procedures and 99m Tc‐labelled tracer in 159. Detection rates for SPIO and 99m Tc were 95·6 and 96·9 per cent respectively ( P = 0·537). All nodes with SPIO uptake were coloured brown. Fewer nodes were retrieved with SPIO (mean 1·35 versus 1·89), regardless of whether blue dye was used ( P < 0·001). Preoperative SPIO injection (58·7 per cent of procedures), a median of 16 (range 2–27) days before the procedure, was associated with a better tracer‐specific detection rate (95·3 versus 86 per cent; P = 0·031) and retrieval of more nodes (mean 1·43 versus 1·03; P < 0·001) than perioperative administration. Skin staining was present in 39·9 per cent of patients, and was related to breast‐conserving surgery and periareolar injection. Conclusion: The use of SPIO alone is a safe alternative, with results comparable to those of the standard dual technique using 99m Tc and blue dye. The efficacy of injection in the preoperative setting simplifies logistics and improves performance. Skin staining can be prevented by a deeper peritumoral injection. Abstract : Simplifies logistics